PENERAPAN AKTIVITAS FUNGSIONAL REKREASI PADA MASA NEW NORMAL UNTUK MENJAGA KESEHATAN LANJUT USIA - Kardi, Ipa Sari; Nasri, Nasri; Ibrahim, Ibrahim; Nopiyanto, Yahya Eko (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2020)
Background: Structural and functional change in the elderly is a process that cannot be stopped, but can be managed, so that it can inhibit the aging process. Technological advances in the digital era 4.0 coupled with the Covid-19 pandemic at the beginning of 2020 make someone, especially the elderly, less mobile. One of the actions that can be taken is implementing recreational functional activities, which are physical activities that are carried out happily with other people, such as family or community. This action is one of the safe and effective ways to help maintain the health of the elderly during the new normal period, so that the elderly are still able to carry out daily physical activities, stay healthy, productive and happy. Recreational functional activities play an important role in the well-being of the elderly and in improving the quality of life of all ages, including the elderly. Purpose: This community service aims to introduce a variety of functional activities that can entertain and delight the elderly. Methods: The method used was counseling and the application of recreational functional activities. Results: Based on the results of blood pressure examinations, it was found that the elderly who had hypertension were (73%) and normal (27%), the BMI measurement showed less weight (20%), normal weight (13%), over weight (20%) , OB I (27%) and OB II (20%). After applying recreational functional activities, there is a good response from the elderly. The elderly feel happier, experience and increase knowledge about simple movements that can stimulate the physical, psychological and social health of the elderly, even if only around the place of residence.